Novel Odoribacter splanchnicus Strain and Its Outer Membrane Vesicles Exert Immunoregulatory Effects in vitro - Hiippala, Kaisa; Barreto, Gonçalo; Burrello, Claudia; Diaz-Basabe, Angelica; Suutarinen, Maiju; Kainulainen, Veera; Bowers, Jolene R.; Lemmer, Darrin; Engelthaler, David M.; Eklund, Kari K.; Facciotti, Federica; Satokari, Reetta (Frontiers in Microbiology, 2020)
Odoribacter splanchnicus, belonging to the order Bacteroidales, is a common, short-chain fatty acid (SCFA) producing member of the human intestinal microbiota. Decreased Odoribacter abundance has been linked to different microbiota-associated diseases, such as non-alcoholic fatty liver disease (NAFLD), cystic fibrosis and inflammatory bowel disease (IBD). The type strain of O. splanchnicus has been genome-sequenced, but otherwise very little is known about this anaerobic bacterium. The species surfaces in many microbiota studies and, consequently, comprehension on its interactions with the host is needed. In this study, we isolated a novel strain of O. splanchnicus from a healthy fecal donor, identified it by genome sequencing and addressed its adhesive, epithelium reinforcing and immunoregulatory properties. Our results show that O. splanchnicus strain 57 is non-adherent to enterocytes or mucus, does not reinforce nor compromise Caco-2 monolayer integrity and harbors penta-acylated, less endotoxic lipid A structure as part of the lipopolysaccharide (LPS). The studies by transmission electron microscopy revealed that O. splanchnicus produces outer membrane vesicles (OMV). O. splanchnicus cells, culture supernatant i.e. spent medium or OMVs did not induce interleukin-8 (IL-8) response in HT-29 enterocyte cells suggesting a very low proinflammatory capacity. On the contrary, the treatment of HT-29 cells with O. splanchnicus cells, spent medium or OMVs prior to exposure to Escherichia coli LPS elicited a significant decrease in IL-8 production as compared to E. coli LPS treatment alone. Moreover, O. splanchnicus spent supernatant induced IL10 production by immune cells, suggesting a broad anti-inflammatory function. Our findings indicate that O. splanchnicus and its effector molecules transported in OMVs could exert anti-inflammatory action in the gut epithelium. Taken together, O. splanchnicus seems to be a commensal with a primarily beneficial interaction with the host.